2019
DOI: 10.1111/evo.13661
|View full text |Cite
|
Sign up to set email alerts
|

Social cues affect quantitative genetic variation and covariation in animal personality traits

Abstract: The social environment is expected to have substantial effects on behavior, and as a consequence, its heritability and evolvability. We investigated these effects by exposing Australian field crickets (Teleogryllus oceanicus) to either silence or recordings of male acoustic sexual signals. We used a combined pedigree and full‐sib/half‐sib breeding design to estimate the repeatability, heritability, and evolvability of behaviors related to boldness, exploration, and activity. All behaviors measured were signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 83 publications
1
12
0
Order By: Relevance
“…By analyzing the gazing directions of the subjects, the authors found that "always obedient" dogs keep gazing at the human partner instead of the food, "always ignorant" dogs do not gaze at the human, and "hesitant" dogs tend to look at the food before they would steal it, but after the deed they gaze rather to that person who might see their action. These findings about the role of individual differences among dogs regarding the effect of a human "audience" on their forbidden activity fits well to the steadily growing interest in animal personalities and individual strategies (e.g., Rudin et al, 2019). One of the basic requirements for sophisticated social interactions is the capacity of individual recognition.…”
Section: Intraspecific Social Behavior and A Touch Of Ontogenysupporting
confidence: 78%
“…By analyzing the gazing directions of the subjects, the authors found that "always obedient" dogs keep gazing at the human partner instead of the food, "always ignorant" dogs do not gaze at the human, and "hesitant" dogs tend to look at the food before they would steal it, but after the deed they gaze rather to that person who might see their action. These findings about the role of individual differences among dogs regarding the effect of a human "audience" on their forbidden activity fits well to the steadily growing interest in animal personalities and individual strategies (e.g., Rudin et al, 2019). One of the basic requirements for sophisticated social interactions is the capacity of individual recognition.…”
Section: Intraspecific Social Behavior and A Touch Of Ontogenysupporting
confidence: 78%
“…The social niche hypothesis posits that behavioral consistency is maintained because social partners constrain each other to maintain stable roles [81,82]. There is some evidence for this; in Australian field crickets (Teleogryllus oceanicus), for instance, the heritability of repeatability is higher when crickets are given social cues [83]. Mate choice may be a particular type of social environment that encourages consistency.…”
Section: Indirect Benefitsmentioning
confidence: 99%
“…Based on statistical differences in the mean value and standard error on distance traveled and speed measured in individuals, these authors concluded that the social environment significantly affected "the repeatable aspect of behavior (i.e., personality), " and that behavioral changes were heritable. However, Rudin et al (91) measured traits in individuals pulled apart from the group rather than on individuals performing within a group. Several studies in the past compared distinct behaviors displayed in ruminants (9,32,39) and authors commonly conclude that "individuals" pertaining to a certain group behave differently to "individuals" pertaining to another group rather than assessing collective behaviors.…”
Section: Grazing Traits Of Herdsmentioning
confidence: 99%